The Gradual Extinction of Transferred Avoidance Stimulus Functions. - Garcia-Guerrero, S.; Dickins, T.; Dickins, D. (Psychological Record, 2014)
We investigated the transfer of conditioned avoidance functions through equivalence relations, and the extinction of these functions, facilitated by verbal prompts. Nine participants acquired three 4-member stimulus equivalence classes using a matching-to-sample procedure. One class stimulus was paired, by classical conditioning, with an aversive tone, which was used in avoidance training of a distinct response. There were two groups: A established the equivalence classes before avoidance training and vice versa for B. During some avoidance trials, each stimulus presentation was followed by the request for a verbal estimation of the probability of the tone. The last trials, run in extinction, included a verbal prompt to corroborate the provided estimation. One participant in each group received no verbal prompts. To negate the necessary reliance on instructions-governed performance, an additional participant completed the experiment with minimal instructions. All participants who had the equivalence training prior to the conditioning showed within-class transfer of avoidance functions, in contrast to the others. All prompted participants who demonstrated transfer showed gradual response extinction, but with a differential gradient. Responding decreased more sharply to the indirectly related stimuli than to the directly paired stimuli. The clinical implications are discussed.